Turn characteristics and energy dissipation in slalom - Reid, R.; Gilgien, M.; Moger, T.; Tjørhom, H.; Haugen, P.; Kipp, R.; Smith, G. (Science and Skiing IV, 2009)
INTRODUCTION: Supej et al. (2005) introduced a method of computing the instantaneous mechanical energy losses of a skier to his surroundings as a measure of turn quality. Characterizing how elements of technique influence energy dissipation may help our understanding of how technique and performance relate. The purpose of this study was to determine the time-course of ski and center of mass (COM) motion characteristics and their relationship to mechanical energy dissipation (EDiss) in Slalom.